The relationship between perceived stress and aggression behavior among individuals with Major Depressive Disorder (MDD) - Noor Hassline Mohamed; Dennis Relojo-Howell; Balan a/l Rathakrishnan (ResearchGate, 2024)
This study examines how perceived stress impacts aggression in individuals diagnosed with Major Depressive Disorder (MDD), specifically looking at the variations between genders. The study utilizes a quantitative questionnaire to investigate the correlation between stress and aggression, as well as the factors that exacerbate this relationship, including the reciprocal linking of stress and aggression. Perceived stress and aggression exhibited a substantial and advantageous correlation (r = 0.62, p < 0.01), suggesting that an increase in aggression was linked to elevated stress levels. 78% of males and 58% of females admitted to frequently exhibiting aggression, while males reported engaging in aggressive behaviors more frequently than females. A reciprocal relationship was discovered, in which escalated aggression led to elevated stress levels and increased stress caused heightened aggression (r = 0.54, p < 0.05), thereby establishing a detrimental feedback cycle. These results indicate that interventions aimed at reducing stress could be especially helpful in decreasing aggression in male MDD patients. This study enhances our comprehension of the dynamics between stress and aggression in MDD and highlights the significance of addressing these aspects in therapy.